2022
DOI: 10.32074/1591-951x-746
|View full text |Cite
|
Sign up to set email alerts
|

Livedoid skin reaction to 2nd dose of mRNA Covid-19 vaccine

Abstract: Summary Skin often represents a target organ for adverse drug reactions and this also applies to the mRNA vaccines against Sars-CoV-2. Here we present a case of extensive livedoid reaction after 2nd dose of BNT162b-2 vaccine with massive blood skin extravasation and no systemic symptoms apart from anemization. The 30-year-old woman developed progressively enlarging livedoid lesions on limbs and abdomen. Histology showed a near-normal epidermis and a very mild interstitial mixed inflammatory infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Eventually, they suggested that the livedoid reaction described could be attributable to an asymptomatic COVID-19 infection at the time of vaccination. However, we clearly reported that the patient repeatedly tested negative in the early period before and after the vaccination 1 . Even with the caveat that rapid antigenic tests yield a high specificity but suboptimal sensitivity, repeated testing should be taken as reasonably reliable of the patient’s immunologic status.…”
Section: Articlementioning
confidence: 82%
“…Eventually, they suggested that the livedoid reaction described could be attributable to an asymptomatic COVID-19 infection at the time of vaccination. However, we clearly reported that the patient repeatedly tested negative in the early period before and after the vaccination 1 . Even with the caveat that rapid antigenic tests yield a high specificity but suboptimal sensitivity, repeated testing should be taken as reasonably reliable of the patient’s immunologic status.…”
Section: Articlementioning
confidence: 82%
“…Long post-COVID vaccination syndrome can occur at any age, in either sex, and with any vaccine brand [ 4 ]. Long-lasting side effects of SARS-CoV-2 vaccines generally include chills/fever, fatigue, lethargy, dizziness, headache, migraine, ageusia, anosmia, visual disturbances, syncope, palpitations, burning sensation, facial paralysis, parosmia, poor sleep quality, seizure, transient ischemic attack, tremor, thyroiditis, nausea, abdominal pain, diarrhea, vomiting, hypoesthesia, neuralgia, paresis, myalgia, muscle cramps, arthralgias, and various skin reactions [ 4 , 9 , 10 , 11 ]. One of the most common long-term side effects of SARS-CoV-2 vaccines, which has been described in several hundred patients, is vaccine-induced immune thrombotic thrombocytopenia (VITT) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…we would like to share ideas on the publication “Livedoid skin reaction to 2nd dose of mRNA Covid-19 vaccine 1 .” Girolami et al observed that no cases of a livedoid skin reaction connected with the Covid-19 vaccine had been documented, and this case demonstrates that a huge livedoid reaction can be another type of skin reaction to the mRNA Covid-19 vaccine 1 . Despite its benefits, the Covid-19 vaccine may be dangerous, which concerns us all.…”
Section: Articlementioning
confidence: 99%